Electoral Cycles in Perceived Corruption: International Empirical Evidence - Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2018)
I examine whether elections influence perceived corruption in the public sector. Perceived corruption in the public sector is measured by the reversed Transparency International's Perception of Corruption Index (CPI). The dataset includes around 100 democracies over the period 2012-2016, a sample for which the CPI is comparable across countries and over time. The results show that the reversed CPI was about 0.4 points higher in election years than in other years, indicating that perceived corruption in the public sector increased before elections. The effect is especially pronounced before early elections (1.0 points) compared to regular elections (0.4 points). Future research needs to investigate why perceived corruption in the public sector increased before elections.
Keywords: C23; D72; H11; K40; 330; perceived corruption; elections; political manipulation; panel data; democracies